Assessment of neonatal, cord, and adult platelet granule trafficking and secretion. (2nd January 2020) - Ngo, Anh T. P.; Sheriff, Jawaad; Rocheleau, Anne D.; Bucher, Matthew; Jones, Kendra R.; Sepp, Anna-Liisa I.; Malone, Lisa E.; Zigomalas, Amanda; Maloyan, Alina; Bahou, Wadie F.; Bluestein, Danny; McCarty, Owen J. T.; et al.
Abstract: Despite the transient hyporeactivity of neonatal platelets, full-term neonates do not display a bleeding tendency, suggesting potential compensatory mechanisms which allow for balanced and efficient neonatal hemostasis. This study aimed to utilize small-volume, whole blood platelet functional assays to assess the neonatal platelet response downstream of the hemostatic platelet agonists thrombin and adenosine diphosphate (ADP). Thrombin activates platelets via the protease-activated receptors (PARs) 1 and 4, whereas ADP signals via the receptors P2Y1 and P2Y12 as a positive feedback mediator of platelet activation. We observed that neonatal and cord blood-derived platelets exhibited diminished PAR1-mediated granule secretion and integrin activation relative to adult platelets, correlating to reduced PAR1 expression by neonatal platelets. PAR4-mediated granule secretion was blunted in neonatal platelets, correlating to lower PAR4 expression as compared to adult platelets, while PAR4 mediated GPIIb/IIIa activation was similar between neonatal and adult platelets. Under high shear stress, cord blood-derived platelets yielded similar thrombin generation rates but reduced phosphatidylserine expression as compared to adult platelets. Interestingly, we observed enhanced P2Y1 /P2Y12 -mediated dense granule trafficking in neonatal platelets relative to adults, although P2Y1 /P2Y12 expression in neonatal, cord, and adult platelets were similar, suggesting that neonatal platelets may employ an ADP-mediated positive feedback loop as a potential compensatory mechanism for neonatal platelet hyporeactivity.